Effect of Precipitation in the Incubation Process of Kemp's Ridley Sea Turtle Nests - Brenes, Óscar (2011)
During the hatching season of Olive Ridley Sea Turtle, from October 11th to November 18th 2010, at playa Tortuga (Ojochal de Osa, Costa Rica), incubation temperature of six clutches transferred into hatchery were monitored. After a rainy period on the first days of November, abnormal egg temperature behavior was recorded by thermo sensors. In order to check egg conditions and embryonic development, totally of eggs were divided in two parts and exhumed. Sudden drop of incubation temperature and embryonic development disruption were direct consequence of extreme precipitations events recorded.